Neural Correlates of Vocal Repertoire in Primates - Dunn, Jacob C.; Smaers, Jeroen B. (Frontiers in Neuroscience, 2018)
Understanding the nature of the relationship between vocal complexity and brain architecture across non-human primates may help elucidate some of the key elements underlying the evolution of human speech. Here we report a positive correlation between vocal repertoire size and the relative size of cortical association areas (governing voluntary control over behavioural output) in non-human primates. We further demonstrate that a hominid grade shift in the relative volume of cortical association areas coincides with a similar grade shift in the hypoglossal nucleus (which is associated with the cranial nerve that innervates the muscles of the tongue). Our results support a qualitative continuity in the neural correlates of vocal repertoire, but a quantitative discontinuity in the extent to which the neural system supporting speech is innervated by cortical association areas in great apes and humans